Socio-demographic, reproductive and clinical profile of women diagnosed with cervical cancer in a tertiary care center in middle Kerala - L., Neha E.; Kondakasseril, Nishi Roshini (International Journal Of Community Medicine And Public Health, 2017)
Background: Cervical cancer is a major health problem in rural India. Barriers to cervical cancer control in our country include a lack of awareness of the disease because of illiteracy, poverty, lack of health education and screening programme. The aim of the study was the clinical profile of women diagnosed with cervical carcinoma in a tertiary care centre in the middle part of Kerala in South India. Methods: This prospective observational study was conducted in the Department of Obstetrics and Gynecology, Government medical college Thrissur for a period of two years from January 2014 to December 2016. The characteristics of patient (age, age at menarche and at marriage, parity, reproductive history, place of residence, income, education status, contraception, screening details, clinical presentation and tumor histopathology and stage were obtained. Data was entered in Excel and analysed. Results: Among7224 new patients seeking care from the department, 104 new cases of carcinoma of uterine cervix were identified (0.71%). Mean age was 58.3±8.4 years. 79% women were from rural area. 73% were illiterate, 88.5% belonged to below poverty line (BPL). Post-menopausal bleeding was the commonest clinical presentation (78.8%). Squamous cell carcinoma was the commonest histologic type (88.5%). 50% had first coitus before age of twenty. 94.3% were not aware of any screening procedures and its importance. 67.31% of cases presented in the advanced stage (stage 2B-1V). 75.81% of late stage disease patients were rural population. 96.77% of late stage disease patients were from below poverty line. Conclusions: Carcinoma cervix is more in the low socioeconomic class and rural elderly presented at an advanced stage. Ignorance about the disease and the lack of awareness of the risk factors, need and availability of screening programmes at low cost in Government health care systems was noteworthy. Government health care policies, health education, effective cancer prevention strategies and early cancer detection programmes are yet to reach the outskirts of rural population in Kerala.